2014
DOI: 10.1186/1471-2458-14-709
|View full text |Cite
|
Sign up to set email alerts
|

Educational differences in cigarette smoking among adult population in Estonia, 1990–2010: does the trend fit the model of tobacco epidemic?

Abstract: BackgroundIn developed countries, smoking spreads through society like an epidemic in which adults from higher socioeconomic groups are the first to adopt and earlier to quit smoking, and in which exists a lag in adoption of smoking between men and women.The objective of this study was to describe trends in daily and occasional smoking, to investigate association between smoking status and education, and to examine if the associations in 1990–2010 in Estonia fit the pattern predicted by the model of tobacco ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
5
12
1
Order By: Relevance
“…Systematic collection of health behavior information started in Estonia in the 1990s. It has been shown that daily smoking patterns among the Estonian adult population generally fit the model of tobacco epidemic in developed countries [ 21 ]. The prevalence of daily smoking among men aged 16–64 years has dropped from 46% in early 1990s to 30% in 2016, while only a slight change has occurred among women (from 18% to 16%) [ 22 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic collection of health behavior information started in Estonia in the 1990s. It has been shown that daily smoking patterns among the Estonian adult population generally fit the model of tobacco epidemic in developed countries [ 21 ]. The prevalence of daily smoking among men aged 16–64 years has dropped from 46% in early 1990s to 30% in 2016, while only a slight change has occurred among women (from 18% to 16%) [ 22 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the proportion of daily smokers in Estonia ranged from 15% among men with higher education to 44% among those with basic education, while among women, the respective proportions were 6% and 29% [ 22 ]. During 1990–2010, the prevalence of daily smoking doubled among women with basic education [ 21 ], which may have contributed to the observed increase in incidence.…”
Section: Discussionmentioning
confidence: 99%
“…as well as emotional factors that inhibit quitting attempts such as low self-confi dence, lack of motivation and social support and diffi culties in funding nicotine replacements. All of these can encourage the individual to experience with smoking tobacco products and adopt this negative behavior (Hiscock, Bauld, & Amos, 2011;Pärna et al, 2014). In contrast, several studies have found the opposite relation as higher hookah use was correlated with higher education levels.…”
Section: Socio-demographic Characteristics and Smoking Among The Entimentioning
confidence: 99%
“…(Yaya et al, 2017). From a study by Pärna et al (2014) it is discovered that smoking activity among men and women with high educational level is likely to be decreasing significantly. 12.…”
Section: The Association Between Perceivedmentioning
confidence: 99%